RESPON PERILAKU AUDITOR DALAM SISTEM PENGUKURAN KINERJA STRATEGI TEHADAP KINERJA KANTOR AKUNTAN PUBLIK - Aziza, Nurna; Salim, Andi Agus (JURNAL FAIRNESS, 2014)
This study examined the behavioral response to the auditor in the Strategic Performance Measurement System (SPMS) to improve performance of public accounting firms. The population in this study were 170 auditors working in public accounting office Sulawesi. The data analysis technique in this study using AMOS 16.0. The results found that the performance measurement system strategy plays into the source of relevant information by the auditor's job in improving the performance of public accounting firms. While ambiquitas and conflict does not affect the behavior of auditors in improving performance.